2014
DOI: 10.18227/1982-8470ragro.v8i2.1737
|View full text |Cite
|
Sign up to set email alerts
|

Validação das unidades arbitrárias do teor de clorofilas obtido em folhas intactas de seringueira.

Abstract: Resumo -A determinação do conteúdo de clorofilas foliares é uma característica de interesse dos ecofisiologistas e dos produtores rurais. Com vistas à utilização prática e nas publicações científicas, objetivou-se com o presente trabalho estabelecer, para folhas de seringueira, equações capazes de converter para o sistema internacional as unidades arbitrárias que expressam os teores de clorofila a (Chl a ), clorofila b (Chl b ) e clorofila total (Chl tot ) obtidos em folhas intactas com uso de clorofilômetro p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Models for chlorophyll and carotenoids (µmol m -2 ) contents in Acca sellowiana leaves and their respective adjusted coefficient of determination (R 2 ), mean absolute error (MAE) and concordance correlation coefficient (CCC) according to the The Clorofilog-1030 device is patented and has been commercially available since 2008. Since then, LP content estimation from FCI readings has been applied for Cotton plants -Gossypium hirsutum (Brito et al, 2011), Castor oil plant -Ricinus communis (Rigon et al, 2012b), Sesame -Sesamum indicum (Rigon et al, 2012a), Jatropha -Jatropha curcas (Rigon et al, 2013), Rubber tree -Hevea brasiliensis (Conforto et al, 2014), Italian ryegrass -Lolium multiflorum (Kaspary et al, 2014), and six Brazilian Atlantic Forest native trees (Vieira Silva, 2014).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Models for chlorophyll and carotenoids (µmol m -2 ) contents in Acca sellowiana leaves and their respective adjusted coefficient of determination (R 2 ), mean absolute error (MAE) and concordance correlation coefficient (CCC) according to the The Clorofilog-1030 device is patented and has been commercially available since 2008. Since then, LP content estimation from FCI readings has been applied for Cotton plants -Gossypium hirsutum (Brito et al, 2011), Castor oil plant -Ricinus communis (Rigon et al, 2012b), Sesame -Sesamum indicum (Rigon et al, 2012a), Jatropha -Jatropha curcas (Rigon et al, 2013), Rubber tree -Hevea brasiliensis (Conforto et al, 2014), Italian ryegrass -Lolium multiflorum (Kaspary et al, 2014), and six Brazilian Atlantic Forest native trees (Vieira Silva, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…LP models of the species listed above were related to FCI a+b, except in Conforto et al (2014) and Vieira Silva (2014), who used individual FCI a, FCI b and FCI a+b readings. In the present study, the modeling was based on FCIa and FCIb combined into the same model, as was observed in Wellburn (1994), who used equations that included both absorbance readings to estimate Chl content, since there is mutual interference between the two Chl wavelengths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation